A sex-disaggregated analysis of the prognostic value of lean type 2 diabetes mellitus in the adult population with acute myocardial infarction - Gwyneth Kong; Jaycie Koh; Jobelle Chia; Bryan Neo; Yiming Chen; Grace Cao; Bryan Chong; Mark Muthiah; Hui Wen Sim; Gavin Ng; Chieh Yang Koo; Chin Meng Khoo; et al. (Cardiovascular Diabetology)
Abstract Background Emerging evidence has demonstrated the unfavourable cardiovascular risk of individuals with lean type 2 diabetes mellitus (T2DM). Our study aims to investigate the prognostic value of lean T2DM in patients with acute myocardial infarction (AMI), stratified by sex. Methods The study cohort examines the clinical characteristics and long-term outcomes of individuals with AMI, stratified by four phenotypes based on T2DM and lean body category—lean T2DM, non-lean T2DM, lean non-T2DM and non-lean non-T2DM. The primary outcome was long-term all-cause mortality. Cox regression model was constructed to investigate the associations of lean and non-lean T2DM phenotypes with mortality, adjusted for age, ethnicity, previous AMI, AMI type, chronic kidney disease, angiotensin converting enzyme inhibitor or angiotensin receptor blockers, beta-blockers, and smoking status. Results A cohort of 9545 AMI patients was examined, with a mean follow-up duration of 3.4 ± 2.4 years. Majority had the non-lean T2DM phenotype (40.4%), followed by non-lean non-T2DM (29.8%), lean non-T2DM (15.9%), and lean T2DM (13.9%). In the T2DM group, one-quarter was lean (N = 1324), while the vast majority (74.5%) was non-lean. Individuals with lean T2DM tended to be female and older. Patients with lean T2DM had the highest rates of heart failure (23.3%, p < 0.001), cardiogenic shock (9.1%, p = 0.036), and long-term all-cause mortality (32.6%, p < 0.001). Cox regression demonstrated that lean T2DM was an independent predictor of mortality (adjusted hazard ratio [aHR] 1.171, 95% CI 1.040–1.319, p = 0.009) after adjustment. The presence of higher mortality risk following AMI was present in males (aHR 1.201, 95% CI 1.037–1.391, p = 0.015), but not in females (aHR 1.066, 95% CI 0.869–1.308, p = 0.538). Conclusions The lean T2DM phenotype was present in one-quarter of the AMI cohort with T2DM. The lean T2DM phenotype was an independent predictor of long-term mortality following AMI, although this association was stronger in males than in females.